The impact of EU common agricultural policy decoupling on farm households: Income vs. investment effects - Davide Viaggi; Meri Raggi; Vittorio Gallerani; Sergio Gomez y Paloma (Intereconomics, 2010)
This paper analyses the effects of decoupling (as introduced in the 2003 reform of the EU Common Agricultural Policy) on farm income and investment behaviour. The results of a dynamic multi-objective household model for 80 farm households in 8 EU countries are analysed and presented through a measure of investment-income elasticity as a reaction to decoupling. The results highlight the differing and contrasting reactions of farm households to policy changes. The main conclusion is that the diversity of farm specialisations and the dynamics of long-term adaptation should be taken into account more explicitly in the evaluation of policy impacts on EU farming systems.
Keywords: 330